Is Your Class Interesting? - A. Qayumov (Researchparks Publishing, 2022)
The article deals with the question of the attractiveness of the educational process as a factor in achieving the didactic goal. The author proposes a number of methods of entertaining and attractiveness of educational and theoretical classes. The methods proposed by the author will not only interest students, but also serve to create a prosperous working climate in the classroom.